An improved approach for the continuous retardation spectra of concrete creep and applications - Zhou, Xinzhu; Bai, Linhong; Rong, Hua; Fan, Xinglang; Zheng, Jianjun; Geng, Yan (Frontiers in Materials, 2024)
Creep is an important physical property of concrete and can lead to additional displacement, stress redistribution, and even cracking in concrete structures, inducing prestress loss of large-scale prestressed concrete structures. When an exponential algorithm is used to calculate the long-term creep of concrete, it is usually necessary to apply the continuous retardation spectra of the material. In the improved approach proposed here, the continuous retardation spectra can be obtained by the Weeks inverse Laplace transform. The CEB MC90 creep model is taken as an example to analyze the computational process, efficiency, and error of the approach. The improved approach is further applied to the ACI 209R-92, JSCE, and GL2000 concrete creep models. Through comparison with other methods, the advantages of the improved approach are illustrated, and some useful conclusions are drawn.